(untitled) (Journal of the College of Basic Education, 2022)
The research deals with the study of transport movement and the reality of traffic in the city of NajafAl-Ashraf; through field monitoring of that movement in the main and secondary streetsDiagnosis of congestion areas in the city and their causes. The field count of the number of vehicles passing through the streets of the study area was completedOf different types and sizes. Convert vehicles into Standard Vehicles (MQs) usingSpecial transactions for this, as the vehicles differ among themselves in terms of their compatibility with the bonus unitsFor standard vehicles, depending on the capacity of the vehicles in terms of passengers, load or length.